Dynamics of Mononychellus tanajoa (Acari: Tetranychidae) in Africa: experimental evidence of the effects of temperature and host plant on population growth rates - Yaninek, J.; Gutierrez, A.P.; Herren, H.R. (1989)
Effects of temperature, season (wet versus dry), plant age, and leaf age on developmental time, fecundity, survivorship, and intrinsic rate of increase (rm) of Mononychellus tanajoa (Bondar) on cassava, Manihot esculenta Crantz, were evaluated using age-specific life table statistics. Preadult developmental times were similar regardless of treatment; however, adult periods, fecundity, and rm were enhanced on young leaves of young plants. Patterns of survivorship and fecundity were similar at 24, 27, and 31°C on a degree-day basis but lower at 20 and 34°C, whereas estimates of rm were similar at all temperatures studied except at 34°C. The lower thermal threshold for development was estimated to be 14.4°C. A simple population model based on empirical rm values predicted larger mite populations on host plants during the wet season than commonly observed. However, when rainfall-induced mortality was added, the large mite populations predicted on wet-season host plants collapsed to levels similar to those observed in the field.